HUBUNGAN PENGETAHUAN SIKAP DAN PRAKTIK PERAWAT TERHADAP UPAYA PENCEGAHAN PASEN JATUH - 1ti Wulandari; Sondang Ratnauli Sianturi (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
The incidence of falling patients has a detrimental effect on the patient, namely the impact ofphysical injury. Fall prevention is one indicator in patient safety. Knowledge, attitudes andpractices of nurses with the ability of nurses play an important role in the implementation ofpatient safety, especially in the prevention of falling patients. This study aims to determine therelationship of knowledge, attitudes and practices of nurses to efforts to prevent patients falling.This research is a quantitative descriptive correlation study. The respondents were nurses whoworked in adult inpatients at Jakarta X Hospital as many as 91 nurses using the accidentalsampling method. The results of univariate research data obtained 46.1% of respondents aged26-35 years, 70% were educated nursing Diploma, 35.1% have worked <5 years in the hospital, 41.8% have competent level, 61.5% have good knowledge, 54.9% have good attitude, 51.6%have good practice and 69.2% have good prevention of falling patients. The results of thebivariate study showed a significant relationship between knowledge (p value 0.016), attitude (pvalue 0.013), practice (p value 0.011) with efforts to prevent patients falling. Respondent haveused the Morse scale and made efforts to prevent patients from falling in the hospital. Theresults of this study are expected to be used to improve the quality of patient care preventionservices related to patient safety (patient safety), especially in inpatient rooms.